Bank performance : change of regime in information ROE conveys - Ulbrich, Marvin Michel (2021)
The financial crisis has shown that the performance measure “return on equity” (ROE) can lead to higher risk for banks. The risks associated with the reliance on a target ROE are well known to regulators and bankers, and yet high ROE targets continue to be proclaimed. The literature has sufficiently analyzed the role of ROE in times of crisis, but so far less has been analyzed about ROE in non-crisis times. Using a bank sample of 920 commercial banks from the U.S. in the period before and after the financial crisis 2007/09, this study investigates the association of ROE with long-term performance and risk expressed as the volatility of stock returns. The obtained results show that while expected ROE is positively associated with market performance in the short term, this effect is unsustainable when considering the significant negative relation with lagged ROE. This finding is particularly strong for the largest 25% banks of the sample. Moreover, contrary to previous literature, ROE is found to have a negative association with risk in non-crisis periods. This can be demonstrated before the crisis but even stronger after the crisis and is robustly observed for large and well-performing banks as well as for different periods. These findings indicate that the markets do not incorporate the risk attached for targeting higher ROE and that in the long run no better performance can be achieved due to high ROE.